Influence of Duct Joint on Modal Parameters of Rectangular Duct - Jade, Nagaraja; Nidheesh, V.; Venkatesham, B. (Journal of Vibration Testing and System Dynamics, 2026)
The present paper discusses influence of duct joint on structural dynamic characteristics (modal parameters) of a rectangular duct. An analytical model is developed to consider the effect of duct joint on modal parameters. The joint condition is modeled as a combination of linear and torsional spring’s stiffness. Developed analytical model is validated with experimental results for a rectangular duct with Pittsburgh lock joint. It is observed that both natural frequencies and mode shapes are in good agreement. For further understanding the influence of duct joint on modal parameters, current analytical model results are compared to duct without joints results and noticed that only antisymmetric mode shapes of duct with joint condition are deviating from ideal duct.